A Modified Electrochemical Model to Account for Mechanical Effects Due to Lithium Intercalation and External Pressure. Issue 2 (19th February 2021) - Zhang, Xiaoxuan; Klinsmann, Markus; Chumakov, Sergei; Li, Xiaobai; Kim, Sun Ung; Metzger, Michael; Besli, Münir M.; Klein, Reinhardt; Linder, Christian; Christensen, Jake
Abstract : For a battery cell, both the porosity of the electrodes/separator and the transport distance of charged species can evolve due to mechanical deformation arising from either lithium intercalation-induced swelling and contraction of the active particles or externally applied mechanical loading. To describe accurately the coupling between mechanical deformation and the cell's electrochemical response, we extend Newman's DualFoil model to allow variable, non-uniform porosities in both electrodes and the separator, which are dynamically updated based on the electrochemical and mechanical states of the battery cell. In addition, the finite deformation theory from continuum mechanics is used to modify the electrochemical transport equations to account for the change of the charged species transport distance. The proposed coupled electrochemomechanical model is tested with a parameterized commercial cell. Our simulation results confirm that mass conservation is satisfied with the new formulation. We further show that mechanical effects have a significant impact on the cell's electrochemical response at high charge/discharge rates.